Uvod v WordPress - Brdnik, Saša; Heričko, Tjaša; Čučko, Špela; Karakatič, Sašo (University of Maribor Press, 2026)
Introduction to WordPress. The textbook provides a comprehensive and systematic introduction to the modern WordPress content management system, aimed at students, teachers, and beginners in website development. It covers the basic concepts of WordPress, from local installation and basic settings to content, user, and media management. Special emphasis is placed on themes, plugins, and customizing functionality, including the basics of developing your own plugins, content types, and taxonomies. The textbook also touches on search engine optimization and best practices for website maintenance. The content is supported by numerous practical examples, screenshots, and explanations that enable a gradual understanding of the material. The textbook guides the reader from the basics to more advanced concepts and enables the independent creation and management of a professional WordPress website. It is intended for both educational use and practical application in real projects.